Peculiarities of acoustic diagnostic methods in pediatric practice (literature review, own research) - Yu.V. Marushko; O.V. Khomych (Сучасна педіатрія: Україна)
Diseases of the respiratory system are among the most common among the population of different age categories. Sound, as a physical phenomenon, is the propagation of longitudinal elastic waves in a medium, for example, in the air. Waves with frequencies below 16 Hz are called infrasound, and above 20,000 Hz are called ultrasound, and these waves cannot be perceived by the human ear. That is why the study of acoustic signals is extremely important for the diagnosis and monitoring of respiratory diseases.